Prevalence and diagnostic value of GPs’ gut feelings for cancer and serious diseases: protocol for a prospective observational study of diagnostic validity - Sebastià March; Magdalena Esteva; María Martín-Rabadán; Bernardino Oliva-Fanlo; David Medina; Gaspar Tamborero; Erik Stolper (BMJ Open)
Introduction Cancer diagnosis in primary care is an important challenge for general practitioners (GPs) due to the relatively low frequency of any single type of cancer and the heterogeneous signs and symptoms that can be present. In addition to analytical reasoning, GPs may become aware of gut feelings (GFs) as they suspect that a patient may have cancer or another serious disease. We aimed to investigate the prevalence and the predictive value of GFs for the diagnosis of cancer and serious diseases.Methods and analysis Prospective observational study of diagnostic validity. Participation will be offered to GPs from Majorca and Zaragoza (Spain). They will recruit all patients with a new reason for encounter during one or two workdays. GPs will complete the Gut Feelings Questionnaire (GFQ). Variables regarding patient, GP and consultation will be collected. Two and 6 months after the first visit, incident diagnoses of cancer or other serious diseases, diagnostic tests performed, referrals and new visits will be recorded. Analysis will include a descriptive analysis of the variables and prevalence of GFs, and the sensitivity, specificity, predictive values and likelihood ratios of the GFs (sense of alarm and sense of reassurance) for diagnosing cancer and other serious diseases, as measured with the GFQ.Ethics and dissemination The study has obtained approval from the Majorcan Primary Care Research Committee and from the Balearic Islands Ethical Committee, with reference number IB 3210/16 PI. The results may help GPs to make more accurate decisions about which patients need further examinations to rule out or to confirm a diagnosis of cancer or a serious disease, and which ones do not. The results will be published as part of the PhD project of the first author and in open access journals, and will be presented at medical conferences.